Real-Time Monitoring System for Temperature, Humidity, and pH for Composting Process - Renny Eka Putri; Ilga Putri Maharani; Irriwad Putri (The University of Lampung, 2025)
Straw is an organic material that has the potential to be used as a basic material for making compost. Rice straw rich in cellulose and lignin, requires a long composting process. The use of IoT as a compost monitoring system is needed to predict the level of compost maturity to meet standards. The aim of this study is to design a composter that is integrated with the development of a monitoring system to obtain data on temperature, humidity, and pH distribution in real time as reference to determine the maturity of straw compost. The monitoring system used based on an ESP32 which was connected to DHT22 sensors, DS18B20, soil moisture sensor V1.2, and soil pH sensor. Data collected from these sensors was transmitted and visualized through the Antares website. The temperature of the composter reached its peak on the 7th day with a value of 56.7°C. The temperature of the compost material reached its highest peak on the 7th day with a value of 42.75°C. The pH value is in the range of 5.5 – 7.4 from the beginning to the end of composting. C/N ratio of compost is 18.13 and is in accordance with SNI 19-7030-2004. Monitoring was conducted for 35 days, in accordance with the estimated compost maturity. Keywords: Humidity, pH, Sensors, Straw, Temperature.